Desenvolvimento de formulações contendo voriconazol encapsulado em nanopartículas lipídicas e promotores químicos de absorção para aplicação tópica na unha - Rocha, Kamilla Amaral David (2015)
The voriconazole (VOR) is an antifungal from the thiazole class, which has a proven action against dermatophytes, main cause of onychomycosis. Topical treatment of pathologies located in the nail is highly desirable, since oral administration of antifungal agents have been shown ineffective. Thus, the goal is the work was the development of nanostructured lipid carriers (NLC) for nail topical administration of the VOR. To quantify VOR in the nail plate, an analytical method was developed and validated by high-performance liquid chromatography (HPLC) with detection in the UV-vis. CLNs were obtained with glyceryl behenate, Miglyol®, polysorbate 80, sorbitan trioleate surfactant, and a cationic cetilpiridíneo chloride (CPC) and different drug loading. Nanoparticles were characterized for medium size, PdI, zeta potential, encapsulation efficiency and recovery, morphology by scanning electron microscopy (SEM), and the stability. Hydration factor of the formulations and permeation enhancers was performed. Analysis of dry and hydrated hooves treated with NLC were achieved by SEM. Release and in vitro permeation studies were performed with unloaded drug (VOR-free) and VOR loaded NLC. The drug quantification method was linear in the concentration range from 0.4 to 40 mg / mL. The limit of quantitation was 400 ng/mL. Furthermore, the method was able to analyze the VOR without suffering interference from components of the nail and NLC. The NLC (n = 3) loaded with drug showed positive surface charge (around +25 mV) and average size of 230 nm. The NLC obtained had 1.75% of drug load, with encapsulation efficiency of 74.52 (+ 2.13)%. Hydration factor studies showed that the formulation with the highest amount of Miglyol was able to hydrate the nail more as well as the urea, which was the best promotor enhancer for nail hydration. NLC developed with and without addition of promoters were stable for a period of 150 days. In vitro release studies showed that the release VOR from the NLC occurs in a controlled manner from the lipid matrix. There was no significant difference in drug penetration when applied CLNs with and without promoter, for the VOR-Free. Although amounts of drug were found more deeply with the use of the CLN in the sample depletion assays, which can facilitate treatment of nail affected by onychomycosis.